If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5 + -3(2x + -4) = 5(4x + 2) + -32 Reorder the terms: 5 + -3(-4 + 2x) = 5(4x + 2) + -32 5 + (-4 * -3 + 2x * -3) = 5(4x + 2) + -32 5 + (12 + -6x) = 5(4x + 2) + -32 Combine like terms: 5 + 12 = 17 17 + -6x = 5(4x + 2) + -32 Reorder the terms: 17 + -6x = 5(2 + 4x) + -32 17 + -6x = (2 * 5 + 4x * 5) + -32 17 + -6x = (10 + 20x) + -32 Reorder the terms: 17 + -6x = 10 + -32 + 20x Combine like terms: 10 + -32 = -22 17 + -6x = -22 + 20x Solving 17 + -6x = -22 + 20x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-20x' to each side of the equation. 17 + -6x + -20x = -22 + 20x + -20x Combine like terms: -6x + -20x = -26x 17 + -26x = -22 + 20x + -20x Combine like terms: 20x + -20x = 0 17 + -26x = -22 + 0 17 + -26x = -22 Add '-17' to each side of the equation. 17 + -17 + -26x = -22 + -17 Combine like terms: 17 + -17 = 0 0 + -26x = -22 + -17 -26x = -22 + -17 Combine like terms: -22 + -17 = -39 -26x = -39 Divide each side by '-26'. x = 1.5 Simplifying x = 1.5
| 80+.10x=132 | | 4x+48=828 | | (x^2-200x+4000log(x)-7200)=0 | | X+12y=23 | | -3a-7a=-3a-6a+7 | | 8u+2-4(-3u+2)=4(u-1) | | 9z+4-8=27 | | M+8=2m+1 | | -2(4s-5)-10=-2(6s+2)-2 | | 2x(x-3)=1+4x | | t^2-6t-4=0 | | F(-3)=9x-5 | | 12X^2-48X+34=0 | | 9y+2x(5y-19)=38 | | .45x+.05(14-x)=.10(79) | | X+.4444=.75 | | 7x+12y=240 | | 1.5*e=6 | | 9y+2x(5x-19)=38 | | 5x-2(3x+5)=10x+32 | | 3p+5=-7+5p | | 5x-3y+12w+2y-4w+7x= | | 2(x-3)-9=6x-4(5+x) | | s+4-2i=0 | | X^2+y^2+4x-14y+4=0 | | 9y+2x(5-19)=38 | | 10+3k=4(8-6k)+5 | | -110=-7(-6m-4)+4m | | 7x-2=a | | 64=16*d | | x=0.6x+984 | | 2(f-6)=8 |